The Strategic Implementation of Green HRM Practices Towards Environmental Sustainability (Journal of Informatics Education and Research, 2023)
Green Human Resource Management (GHRM) serves as a pivotal strategy aimed at cultivating a workforce that embraces and integrates environmentally friendly principles, all while advancing the company's eco-conscious objectives throughout the various facets of HRM. This encompasses activities such as green recruitment, green training, environmental awareness, within the company's human capital framework. Key components of GHRM include preservation of knowledgeable investment and nurturing eco-friendly HR practices. Researcher have delved into the significance of GHRM in implanting an ecologically cognizant mindset among employees, though this field of study is still evolving. With industries progressively arranging ecological and green management, their areas and policies have accommodated to reflect this shift. The global economic landscape has transitioned from traditional structures to a contemporary, capacity-based model, wherein both environmental economics and conservation management play vital roles. Amid corporate globalization, organizations are placing heightened emphasis on eco-friendly objectives, necessitating strategic tools like GHRM to create and sustain green workplaces and practices. This study highlights on findings underscore the optimistic impact of GHRM practices, such as green hiring, on the sustainable performance in manufacturing organizations through quantitative approach with 158 participants. The outcomes highlight that adopting practices like green hiring contributes to the sustainable well-being of the environment, the economy, and society at large.